2020
DOI: 10.17580/cisisr.2020.02.10
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of microstructural inhomogeneity by thickness of hot-rolled plates made of cold-resistant low-alloy steel for Arctic applications

Abstract: A technique to assess microstructural anisotropy assessing by the thickness of the plate steel based on the texture analysis of the image has been developed. This technique provides for the anisotropy assessment at two dimensional levels: in the short-distance and long-distance neighborhoods, which characterize the elongation along the rolling direction of fine and coarse structural constituents, respectively. The practical approval results of this technique in the study of the microstructural heterogeneity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…It was shown in several researches that non-tempered martensite is characterized by increased resistance against different kinds of wear, which is connected in the conditions of friction loading with development of the processes of dynamic ageing that can lead to efficient fixing of dislocations and intensive strengthening [19][20][21][22][23].…”
Section: Results Of the Research And Discussionmentioning
confidence: 99%
“…It was shown in several researches that non-tempered martensite is characterized by increased resistance against different kinds of wear, which is connected in the conditions of friction loading with development of the processes of dynamic ageing that can lead to efficient fixing of dislocations and intensive strengthening [19][20][21][22][23].…”
Section: Results Of the Research And Discussionmentioning
confidence: 99%
“…Of course, characteristics of bainite can be determined using modern methods based on the use of scanning electron microscopy and backscattered electron diffraction. However, in this work, with the use of special etching methods based on hydrofluoric acid, characteristics of lath-morphology bainite were evaluated via optical methods [22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…To establish the quantitative relationship between the parameters of the microstructure and the properties of rolled products, the quantitative analysis of the microstructure of rolled products with the thickness of 10 mm was carried out, using both reference scales and automated methods through the image analysis. Non-metallic inclusions were assessed according to the ASTM E1245-03 standard; the grain size (structural element) was assessed according to the ASTM E1382-97 standard; microstructural banding in accordance with GOST 5640; structural anisotropy and the central segregation region (segregation band) according to scales in accordance with the GB T 13298-2015 standard, as well as morphological and stereological parameters of bainitic colonies [12,20,21].…”
Section: Methodsmentioning
confidence: 99%
“…Xie et al studied the influence of holding time on carbide size and distribution in 960 Mpa grade low alloy steel, and found that prolonging the holding time leads to the coarsening of carbides [19]. in terms of research on the models and characterization of material grain size distribution [20][21][22][23], Yu et al studied the non-uniformity of microstructure in both 2 and 3 mm-thick Dp600 thin plates, and established models for accurately describing the non-uniform distribution of microstructure in thin plate [20]. Kazakov et al investigated the microstructural non-uniformity of 25-70 mm hot-rolled thick plates and proposed a method to evaluate microstructural anisotropy [21].…”
Section: Introductionmentioning
confidence: 99%